Answer :

Given:-


Take


LHS



We know that, Formula



Thus,






5x = –1 + 6x2


6x2 – 5x – 1 = 0


6x2 – 6x + x – 1 = 0


6x(x – 1) + 1(x – 1) = 0


(6x + 1)(x – 1) = 0


6x + 1 = 0 or x – 1 = 0



Since,



So,


is the root of the given equation


Therefore,



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers